Pengabdian Masyarakat Melalui Kuliah Kerja Nyata Terpadu (KKNT) Di Kelurahan Waisai Kota Distrik Kota Waisai - Maelany, Megawaty; Musdalifa, Musdalifa; Andriani, Yulia; Fatimah, Husnul; Nurrahiya; intan, Nur; Masseni (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2024)
The aim of implementing integrated real work courses (KKNT) is to provide experience for students, broaden their horizons, improve their skills, independence, responsibility, ability to solve problems in society and be able to practice the tri dharma of higher education. The methods used are observation, interviews and documentation methods. This KKNT activity is carried out for approximately 4 months, during which time it is hoped that students will be able to mingle with the community and be able to harmonize what they have received in college with what is happening in the field. In this KKNT, many programs have been successfully completed, including making rubbish bins, making boundaries and mosque name boards, community service, planting trees and so on.